2016
DOI: 10.1371/journal.pone.0154711
|View full text |Cite
|
Sign up to set email alerts
|

Minimum Field Strength Simulator for Proton Density Weighted MRI

Abstract: ObjectiveTo develop and evaluate a framework for simulating low-field proton-density weighted MRI acquisitions based on high-field acquisitions, which could be used to predict the minimum B0 field strength requirements for MRI techniques. This framework would be particularly useful in the evaluation of de-noising and constrained reconstruction techniques.Materials and MethodsGiven MRI raw data, lower field MRI acquisitions can be simulated based on the signal and noise scaling with field strength. Certain assu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 31 publications
0
16
0
Order By: Relevance
“…90–92 The use of iterative constrained reconstruction algorithms have been shown to improve the SNR from low field simulated measurements, and these hold great potential in future use of upright low field scanners for RT-MRI of the upper airway. 93 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…90–92 The use of iterative constrained reconstruction algorithms have been shown to improve the SNR from low field simulated measurements, and these hold great potential in future use of upright low field scanners for RT-MRI of the upper airway. 93 …”
Section: Discussionmentioning
confidence: 99%
“…[90][91][92] The use of iterative constrained reconstruction algorithms have been shown to improve the SNR from low field simulated measurements, and these hold great potential in future use of upright low field scanners for RT-MRI of the upper airway. 93 The clinical role of RT-MRI in the assessment of abnormal vocal tract and upper airway dynamics has not yet been determined, and remains an exciting area for investigation. VPI, swallowing-aspiration, and obstructive apnea are among the most compelling initial applications due to the prevalence of these conditions, and the lack of safe nonionizing alternatives.…”
Section: Discussionmentioning
confidence: 99%
“…2 As discussed in the accelerated readouts section, these techniques can be used to reduce the motion sensitivity. In simulations, it has been demonstrated that such techniques can be used, even at low field, to image upper airway displacement in real time …”
Section: New Acquisition Strategiesmentioning
confidence: 99%
“…In simulations, it has been demonstrated that such techniques can be used, even at low field, to image upper airway displacement in real time. 73…”
Section: New Acquisition Strategiesmentioning
confidence: 99%
“…The dataset in [8], [24] is however not publicly available. To circumvent this, we simulate low field MR images for the ADNI dataset using a recently developed technique in [47]. Certain assumptions are made by the authors of [47]: 1.)…”
Section: E Enhancing Low Field Mr Imagesmentioning
confidence: 99%